2015
DOI: 10.1007/s00204-015-1595-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic analyses to scrutinize the assumption that genotoxic PAHs exert effects via a common mode of action

Abstract: In this study, the accuracy of the assumption that genotoxic, carcinogenic polycyclic aromatic hydrocarbons (PAHs) act via similar mechanisms of action as benzo(a)pyrene (BaP), the reference PAH used in the human health risk assessment of PAH-containing complex mixtures, was investigated. Adult male Muta™Mouse were gavaged for 28 days with seven individual, genotoxic PAHs. Global gene expression profiles in forestomach, liver, and lung (target tissues of exposure) were determined at 3 days post-exposure. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…We used an alveolar type II cell line from mouse as a surrogate to determine the actions of these combined PAHs in lung tissue and in the future will use mouse models as well as human cell lines to further validate these findings. Our studies together with others (Labib et al 2016 ) support the need for these additional studies to determine if re-evaluation of IARC categorization for these LMW PAHs is warranted due to the likelihood that they are co-carcinogenic or tumor promoters.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We used an alveolar type II cell line from mouse as a surrogate to determine the actions of these combined PAHs in lung tissue and in the future will use mouse models as well as human cell lines to further validate these findings. Our studies together with others (Labib et al 2016 ) support the need for these additional studies to determine if re-evaluation of IARC categorization for these LMW PAHs is warranted due to the likelihood that they are co-carcinogenic or tumor promoters.…”
Section: Discussionsupporting
confidence: 75%
“…A recent paper indicated that different carcinogenic PAHs have different MOAs, via studies using transcriptomics (Labib et al 2016 ). Carcinogenic HMW PAHs had different transcript profiles and while they all induced DNA adducts, the MOAs for carcinogenicity were not the same, thus cannot be based on B[ a ]P alone.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has previously been demonstrated in several mouse models that the tissues examined here have constitutive or inducible levels of CYP1A1, 1A2, and/or 1B1, all of which are known to convert PAHs to DNA‐reactive metabolites [Choudhary et al, ; Nebert et al, ; Uno et al, ; Renaud et al, ; Nebert et al, ; Arlt et al, ]. Moreover, our lab group has previously demonstrated induction of CYP1A1 and 1B1 in Muta™Mouse lung and liver following an identical oral exposure regime to several individual PAHs [Labib et al, ].…”
Section: Discussionmentioning
confidence: 66%
“…Lung data were previously published in Labib et al (2012) . DBahA lacZ mutant frequency data for liver only were previously published in Malik et al (2013) , and lung lacZ and DNA adduct data for BaA, DBahA, BbF, CHRY, BkF, INDENO, and BghiP were recently published in Labib et al (2015) . These data were re-analysed in the manner stated above to permit direct comparison to the results generated specifically for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The PAHs examined herein are benz( a )anthracene (BaA; IARC Group 2B), dibenz( a , h )anthracene (DBahA; IARC Group 2A), benzo( b )fluoranthene (BbF; IARC Group 2B), chrysene (CHRY; IARC Group 2B), benzo( k )fluoranthene (BkF; IARC Group 2B), indeno(1,2,3- c , d )pyrene (INDENO, IARC Group 2B), and DBalP (IARC Group 2A; also known as dibenzo( def , p )chrysene), and BghiP (IARC Group 3). The previously published results for BaP (IARC Group 1) ( Labib et al, 2012 , Lemieux et al, 2011 ), the liver lacZ mutation and DNA adduct data for DBahA ( Malik et al, 2013 ), as well as lung lacZ mutation and DNA adduct data recently published by Labib et al (2015) (for all compounds except DBalP) are also included in our analyses.…”
Section: Introductionmentioning
confidence: 99%